Anti-hyperlgycemic activity of Basella rubra leaf extract in alloxan-induced diabetic mice - Agaran, Jenny A.; Pugal, Bon Derryl G. (2009)
Diabetes melitus is a disease which result from insufficient production or decreased insulin sensitivity. It is with the increasing incidence of this disease why researchers thrust towards looking for plant compounds having anti-hyperglycemic activities. In this research, triterpenoid was extracted from the leaves of Basella rubra and was tested for its anti-hyperglycemic activity at doses of 20,40 and 80 ug/g body weight of 28-hour alloxan-induced diabetic mice (300ug/g body weight). The triterpenoid obtained was 0.5123 g or 5.82% of the crude leaf extract (8.808g). The blood glucose levels of mice were determined within two hours at 30 minute intervals. Using statistical analysis, the triterpenoid leaf extract at 20,40, 80 ug/g body weight showed significant percent blood glucose reduction at 1.5 h and continued for 2 h (p<0.05). This suggest that the on set of the effectiveness of the extract is at .5h. The highest significant percent blood glucose reduction by 63.74% was at the dose of 80 ug/g body weight of the extract. It is also at a dose of 80 ug/g body weight of the extract that is seen most comparable to the effect of Metformin HCI. The results obtained from the study suggest that triterpenoids from Basella rubra leaves posses anti-hyperglycemic activity -- Author's abstract.